WADY WRODZONEThoracoscopic closure of patent ductus arteriosus in 2 premature infants weighing 700 and 800 g - Kołtowski, Piotr; Patkowski, Dariusz; Adamus, Jacek; Wesnerowicz, Anna; Cichoń, Romuald (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Patent ductus arteriosus (PDA) is a common congenital disorder. Currently ductus Botalli closure is the realm of invasive cardiology. Extremely low-birth-weight (ELBW) premature infants (< 1000 g) are a very special group of patients. The presence of ductus arteriosus among this group is significantly higher than in the rest of the population. Inability to perform ductus Botalli closure with percutaneous methods causes that administration of indomethacin (despite multiple side effects) or surgery is the treatment of choice. We admitted 2 patients born in the 24 th week of pregnancy with a weight 702 g and 804 g. The patients were transferred to the pediatric intensive care ward on the first or second day after the procedure. Potentially reduced invasiveness of this method seems to be more adequate than traditional lateral thoracotomy. We believe that this will be the method of choice in the treatment of patent ductus arteriosus in premature infants.